Painting and literature in Luis Mucillo’s Piano Concert Hoffmanneske Geschichte: das klingende Glas. (Revista Argentina de Musicología, 2009)
Luis Mucillo’s Piano Concerto, Hoffmanneske Geschichte: das klingende Glas, developed from a piano piece, draws its main inspiration from a painting by Paul Klee which, in turn, points to E. T. A. Hoffmann. Placed in a net of influences that includes, among others, Rilke, Schoenberg, Mozart, and Schumann, this musical work seems particularly appropriate to study the phenomenon of the correspondence between the arts. Based on some interviews with the composer, as well as on a comparative analysis of the Concerto and the pictorial and literary works that contributed to its genesis, this article focuses on the transformation of literary and pictorial elements into musical gestures, techniques and materials, offering an insight into the intertextual relationships that emerge from it.
Keywords: Mucillo; Klee; Hoffmann; intertext; painting